Growth and Reforms in Latin America : A Survey of Facts and Arguments - Zettelmeyer, Jeromin (IMF Working Papers; Working Paper ;, 2006)
This paper presents a number of facts about growth in Latin America, and shows how critical correlates of growth have evolved over time. In comparison with other regions, Latin America has consistently exhibited higher macroeconomic volatility, lower openness, and higher income inequality, though openness and macroeconomic stability have improved since the early 1990s. The paper then discusses three views of why reforms have not led to higher growth in Latin America: that reforms have gone too far; that reforms have not gone far enough; and that reforms have missed the point.